Embark of Walton group of industries as a rising competitor for domestic and global manufacturers of electronic appliances - Rafat – Ul - Alam, MD. (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.